Evaluate XML Data Performance In WAP / Mohd Abdul Shakor Mohd Zamri - Mohd Zamri, Mohd Abdul Shakor (2004)
In today's information society, users are overwhelmed by the information with which they are confronted on a dally basis. Analysts predict that, within a couple of years, nearly one billion mobile phones, personal digital assistants and handheld computers will be connected to the Internet. According to The Strategis Group, there will be more than 530 million wireless subscribers by the year 2001. New estimates report that the number of wireless subscribers will break the one billion mark by 2004, and a "substantial portion of the phones sold that year will have multimedia capabilities." These multimedia capabilities include the ability to retrieve Email, and push and pull information from the Internet. Furthermore the wireless Web promises to give people the power to access information and conduct transactions anytime, anywhere. However, for developer for the wireless application, this may present a problem. The main problems that faced by the developer are to develop a WAP service that capable to speedup data transmission In effective and efficient way. This research intends to evaluate the data transmission especially for the wap application that had been written in wml In order to find the factor that give a deep Impact to the data transmission. Other than that, this research also will propose a new guideline In developing WML coding and also wml script in order to improve data transmission and reduces the failure of the functionality. The findings of this research are hope be able to shed some light for all of us